Assembly behaviour and thermodynamics of the mixture of cetyltrimethylammonium bromide and bovine serum albumin in aqueous and aqua-ethylene glycol mixed solvents media at several temperatures. (19th March 2022) - Hoque, Md. Anamul; Mahbub, Shamim; Khan, Javed Masood; R. Joy, Md. Tuhinur; Khan, Mohammed Abdullah; Kumar, Dileep; Ahmad, Anis; Ahmed, Mohammad Z.
Abstract : The aggregation of the mixture of cetyltrimethylammonium bromide (CTAB) and bovine serum albumin (BSA) in aqueous and aq. ethylene glycol (EG) media has been carried out conductometrically at numerous temperatures. Conductivity values of CTAB have been changed with the concentration of CTAB and the values also experience a change with the presence of BSA, change of BSA concentration, variation of EG contents as well as the experimental temperatures. The critical micelle concentration ( CMC ) and the extent of micelle dissociation ( α ) were evaluated graphically plotting the specific conductivity against the CTAB concentration. The CTAB aggregation happens lately in the appearance of BSA. Also, the CMC values of CTAB + BSA experience an upsurge with the rise of BSA contents. The CMC values of the mixture of CTAB and BSA have been obtained to be higher in extents in aq. EG solution in contrast to water medium. In all of the circumstances inspected, the micellisation of the CTAB + BSA mixture is spontaneous (negative Δ G 0 m values). Depending on the ΔH 0 m and Δ S 0 m values for the CTAB + BSA mixture, the recommended forces between CTAB and BSA are electrostatic interaction (hydrogen bonding and ion-dipole interactions) and hydrophobic interactions. GRAPHICAL ABSTRACT: UF0001